Habituasi Protokol Kesehatan Warga Desa Giri Kapubaten Gresik - Dewi, Andini Nurrahmah (Paradigma, 2022)
The COVID-19 pandemic has an impact on various aspects of life ranging from health, social, economic, education and others. The government makes regulations for implementing health protocols that must be carried out by the entire community in order to reduce the transmission of COVID-19. One area in Indonesia that has the potential to become a high transmission of COVID-19 is Gresik Regency because it is one of the regencies in Greater Surabaya. Gresik has Sunan Giri Religious Tourism which is located in Giri Village. These tours are visited by many local and foreign tourists, so that the mobility of the residents is quite high coupled with the majority of the citizens working as entrepreneurs who interact with many buyers. Therefore, this study aims to analyze the habituation of the COVID-19 health protocol for the residents of Giri Village. This study uses a qualitative method with the perspective of Pierre Bourdieu's Habituation theory to analyze. The collection of subjects used a purposive technique with the criteria of entrepreneurs who were around Sunan Giri Tourism and became COVID-19 survivors. The results showed that residents felt a change in the implementation of health protocols after they were infected with COVID-19. In addition, after experiencing the COVID-19 pandemic, residents have implemented their own health protocols such as only wearing masks when in a crowd because of the declining number of COVID-19 cases. Keywords : Habituation, Health Protocol, Giri Villager